ORZECZNICTWO TRYBUNAŁU SPRAWIEDLIWOŚCI WSPÓLNOT EUROPEJSKICH DOTYCZĄCE KONWENCJI BRUKSELSKIEJ A KONWENCJA Z LUGANO - Włosińska, Aleksandra (Wydział Prawa i Administracji UAM, 1999)
The Author confronts two international legal acts - the Convention signed in Brussels on September 27,1968, and the Convention signed in Lugano on September 16, 1988 - both relating to legal system o f the European Economic Communities and of the European Free Trade Association (EFTA) The texts of the two documents are related first of all to: the range of jurisdiction of courts, the recognition of judicial decisions taken by foreign courts, a simplification of proceedings at a court, the executability of foreign judicial decisions, the interdiction of re-examining foreign judicial decision as in its merits. Next the Author analyses judicial decisions of the Court o f Justice o f European Communities as being fundamental mean serving for univocal interpretation of the Brussels Convention and then also the controversies among the States-members of the EFTA because of competence of the Tribunal against the background of provisions of the Lugano Convention (being done that this Tribunal is an organ of European Communities and not of the EFTA). Finally, the Author id occupied with application of the Lugano Convention by courts of States being not EFTA members.
JUDICIAL DECISIONS OF THE EUROPEAN COMMUNITIES’ COURT OF JUSTICE CONCERNING THE BRUSSELS CONVENTION AND THE LUGANO CONVENTION